PENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN PADA ANAK (5-6) MELALUI KEGIATAN PENDAMPINGAN PARENTING - Elih Solihatulmillah (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2019)
This study generally aims to obtain information and data on the reading ability of beginners to read early childhood 5-6. This research is a classroom action Research conducted at KOBER PAUD As.Syifa having the address at Jalan. Btn. Junti Asri Blok C.2. No. 2 villages. Junti District Jawilan, Banten District. The data collection technique is a reading ability for beginners of early childhood 5-6. The results showed that 1) there was an increase in the ability to read beginners early childhood 5-6 with parenting assistance; 2) parenting facilitation activities include mothers holding together with the teacher motivating children in the learning process.